Feasibility of the estimation of octanol-water distribution coefficients of acidic drugs by microemulsion electrokinetic chromatography - Alejandro Fernández-Pumarega1; Susana Amézqueta1; Elisabet Fuguet; Martí Rosés (International Association of Physical Chemists (IAPC), 2018)
Previous studies have shown that a microemulsion electrokinetic chromatography (MEEKC) system can estimate the logarithm of the octanol-water partition coefficient (log Po/w) of neutral solutes. In the present work, the applicability of the method to partially and fully ionized acids has been evaluated. Naproxen, a monoprotic acid, has been used as test solute. The retention factor (k) of this compound has been measured in MEEKC at several values of pH and the retention factor-pH profile has been established. As log Po/w correlates with log kMEEKC for neutral compounds, this correlation has been used to estimate the logarithm of the octanol-water partition coefficient of the neutral (log Po/w(HA)), and the fully ionized (log P o/w(A-)) forms of naproxen. Then, the logarithm of the octanol-water distribution coefficient (log Do/w) of the partially ionized form of the acid has been estimated. The comparison of the estimated values with the ones obtained experimentally using the classical procedures, such as the shake-flask method, shows differences under 0.4 log Do/w units either if the acid is partially ionized or in its neutral form in the most part of the pH range. However, the method overestimates the log Do/w of the highly (>99.5 %) or fully ionized form of naproxen.